Elaboración e implementación del curso virtual de la asignatura de biología, para el tercer año de bachillerato general unificado en ciencias del colegio nacional 26 de Noviembre de la ciudad de Zaruma - Castro Pontón, Diana Carmita (2014)
Today the use of Information Technology and Communication (ICT) in the classroom, have become a major in Education tool, however there are still institutions that do not make use of them, through ignorance, lack technology infrastructure, or lack of educational software. For this reason the proposal was made to implement a virtual biology course. In zone 7, province of El Oro, Canton Zaruma, urban parish Zaruma, particularly in the National College " November 26 ", first an interview with was scheduled to teachers of the subject of biology, in order to meet the difficulties when teaching their classes, based on this information, the online course was developed and finally a survey was conducted to teachers and students in order to share their experiences with the virtual learning platform. The planning of the subject of Biology were performed based on the guidelines of the Ministry of Education of Ecuador from a constructivist approach; the same that were structured teacher support plans: annual, unit and Role thereof containing blocks of the subject of Biology, with their respective topics, based on these objectives, resources, methods established and techniques. The virtual platform was developed with Moodle, it facilitated the process of teaching - learning, allowing teachers and students interact with the course in a dynamic, arousing interest and curiosity for the activities.